Acute kidney injury after cardiac surgery in the North of Iran - Jalal Kheirkhah; Zahra Ahmadnia; Arsalan Salari; Heidar Dadkhah; Seyedeh Shiva Modallalkar; Tolou Hasandokht (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Acute renal failure is a well-known complication in patients after cardiac surgery. Objectives: The determination of disease-causing factors with the aim of identifying patients at high-risk and implementing preventive care pre- and postoperatively to reduce the incidence of acute kidney injury (AKI) in patients after cardiac surgery. Patients and Methods: The present cross-sectional research was carried out on 512 adult patients who underwent cardiac surgery between 2015 and 2016 in our tertiary center. Demographic and laboratory data of patients were obtained using a checklist. AKI is defined as an increase of at least 0.3 mg/dL in creatinine (Cr) over 48 hours and one week after surgery according to acute kidney injury network (AKIN) and RIFLE (risk, injury, failure, loss of kidney function, and end-stage renal failure) criteria before surgery. All data were analyzed by SPSS version 1, and P value <0.05 was considered significant. Results: In this study we found, AKI risk profiles including serum Cr level [OR = 3.24, 95% CI = 1.92 -12.48, P = 0.001], fasting blood glucose [OR = 1.22, 95% CI = 1.09 -1.92, P = 0.03] and hemoglobin (Hb) before surgery (OR = 0.59, 95% CI = 0.08 -0.87, P = 0.04) were significantly associated with increased risk of acute renal injury (logistic regression analysis). Conclusion: The results indicated that changes in serum Cr level, fasting blood glucose and plasma Hb before cardiac surgery might be considered as the risk factors for AKI after cardiac surgery.